The age dynamics of vineyards: Past trends affecting the future - Anna Carbone; Luisangela Quici; Giovanni Pica (Wine Economics and Policy, 2019)
The paper introduces a modified version of the demographic balance equation commonly used in human demography in the study of populations of permanent crops. The proposed methodology is then applied to analyzing the evolution of the Italian vineyard. In short, the study measures different factors that have had an impact on the extension of the Italian vineyard and on its age structure such as the reduced investments in new plantations; the massive early explant and also the extended life of the vineyards since they are kept in production well beyond the conventional limit of their economic life. Results show that the reduction of the area cultivated with grapes in Italy is due to different reasons, some of which relate to the past while others mirror more recent behaviors of vine growers. The methodology also allows the prediction of tendencies in the future. Three scenarios are built, based on different hypothesis about new investments and explantation rates that account for the wine EU CMO 2013-2030. Projections show, that in the next decades, both the extension of cultivated area and plant age will be deeply influenced by choices that had been made even decades before. Comparing the results obtained under the different hypothesis, helps to assess the range of possible impacts of the new policy framework. In an increasingly global and competitive market, the analysis proposed provides original insights on some future waves in the wine industry both to policy makers and stakeholders. This awareness is especially needed in order to put in place strategies aimed at avoiding supply-demand mismatches in a sector where supply moves slowly while demand trends are fast and almost unpredictable.
Keywords: 330; Demographic trends; Future scenarios; Italian vineyards